Hospice-at-home nurses' experiences of caring for patients. (2nd February 2021) - Jameson, Catherine
Abstract : Background: The demand for hospice-at-home (HH) nurses is increasing due to an ageing global population and many people preferring to die at home. Therefore, the retention of existing HH nurses is vital. Aims: This paper explores HH nurses' experiences of caring for dying patients to discover the factors that enable them to maintain their enthusiasm for their work, and cope with the challenges of working in a patient's home. Methods: This qualitative study consisted of multiple unstructured interviews with 16 HH nurses conducted in England. Findings: The interviews show that HH nurses: use a broad range of coping mechanisms; encounter intense, complex, unpredictable and ethically unclear challenges; identify a need for more support; and love their job. Conclusion: In order for nurses to continue to enjoy their job, extra support to incorporate protected time for debriefing at the end of an HH nurse's shift is needed. Nurses also need training to develop positive coping skills, external supervision on a one-to-one basis as needed, and have their value demonstrated, by their employers and managers recognising and acknowledging them. These factors are likely to facilitate in the retention of employment of HH nurses.